Good Sport Governance: Perspektif Teoretis, Yuridis dan Kontekstualisasinya di Indonesia - Wijaya, Endra; Silvana, Nina (Jurnal Hukum & Pembangunan, 2024)
The sport sector is not only a matter of health or the pride of a nation. More than that, the sport is closely related to social welfare aspect. Therefore, it needs to be managed optimally by referring to the principles of good governance specifically in the sport sector. This study discusses the concept of Good Sport Governance, both from theoretical and legal perspectives, and its contextualization in Indonesia. This study uses doctrinal legal research methods and utilizes secondary data. Data analysis is carried out qualitatively using conceptual and statute approaches. This study concludes that the principles of Good Sport Governance need to be applied in managing the sport sector in Indonesia because in fact the dynamics of the sport sector in Indonesia still require a lot of improvement. Good Sport Governance contains several main principles, such as the principles of transparency, democracy, control and solidarity. Furthermore, in the Indonesian context, Good Sport Governance is also equipped with the principle of deliberative discussion.